Volume 2: Fora 2012
DOI: 10.1115/fedsm2012-72378
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation of Multiple Bubble Entrainment and Interactions With a Traveling Vortex Ring

Abstract: Bubble interactions with vortical structures are important to better understand the mechanisms of bubble induced boundary layer drag reduction and chemical mixing. Traditionally, many studies of disperse bubble or particle-laden flows have utilized an Euler-Lagrange two-way coupling approach, wherein the dispersed phase is assumed subgrid and its dynamics is modeled. In this work, results on full three-dimensional simulation of traveling vortex ring together with a few microbubbles are presented utilizing a vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It was found that the existence of the bubble resulted in the distortion of the vortex. Cihonski et al 20,21 further extended the study to three-dimensional simulation of travelling vortex ring together with a few micro-bubbles using a volumetric coupling approach. However, in their model, they ignored bubble oscillations and just took bubbles as spheres with gas density.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the existence of the bubble resulted in the distortion of the vortex. Cihonski et al 20,21 further extended the study to three-dimensional simulation of travelling vortex ring together with a few micro-bubbles using a volumetric coupling approach. However, in their model, they ignored bubble oscillations and just took bubbles as spheres with gas density.…”
Section: Introductionmentioning
confidence: 99%